Adaptation and validation of the racial & ethnic microaggressions scale (REMS) Indonesian version - Irawan, Andi Wahyu; Dwisona, Dwisona; Lestari, Mardi (University of Muhammadiyah Malang, 2025)
This study aims to adapt and validate The Racial & Ethnic Microaggressions Scale (REMS) into Indonesian in response to the lack of instruments that measure racial and ethnic microaggressions within the Indonesian context. The study involves the translation of REMS into Indonesian and instrument validation using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) with a sample of 526 participants from various cultural backgrounds. The EFA results showed a Kaiser-Meyer-Olkin (KMO) value of 0.939 and a Bartlett's test value of 0.00, indicating that the data were suitable for factor analysis. In addition, five factors with eigenvalues > 1.0 and factor loadings > 0.30 were identified. Further CFA analysis indicated that the aspects of the Assumptions of Inferiority and Second-Class Citizen and Assumptions of Criminality had good validity with an Average Variance Extracted (AVE) > 0.5 and high reliability with Composite Reliability (CR) and Cronbach's Alpha (CA) > 0.7. In contrast, the aspects of Microinvalidations and Environmental Microaggressions showed lower validity and reliability. Therefore, this study provides a valid and reliable instrument for measuring racial and ethnic microaggressions in the Indonesian context, which can assist researchers and practitioners in identifying, understanding, and developing more effective interventions to address microaggressions in a multicultural society.